Specific detection of Candida albicans and Candida krusei by singleplex intercalating-dye based qPCR - Robiatul Adawiyah, Rachma Allysa Vidya Putri Augustine, Syifa Annisa, Firyal Fairuztsana Nugraha, Nabila Meuthia Arifin, Heri Setiawan, Anna Rozaliyani, Muhareva Raekiansyah, Ken Watanabe, Ratika Rahmasari (Journal of Applied Pharmaceutical Science, 2025)
Currently, mixed infections involving Candida albicans and Candida krusei have become increasingly common in cases of invasive candidiasis. Accurate identification of Candida species using polymerase chain reaction (PCR) is crucial for effective management, as timely and appropriate antifungal therapy is essential. Real-time PCR using the double-stranded DNA binding intercalating dye, offers several advantages over TaqMan chemistry, as it does not require the synthesis of specific probes, making it a more accessible option. In this study, we developed and evaluated specific primers, Ca2 and Ca3, targeting the ITS1/ITS2 regions of C. albicans and C. krusei, respectively, using intercalating dye SYBR Green chemistry. Our results demonstrate that the Ca2 primer specifically detects C. albicans, while the Ca3 primer accurately identifies C. krusei in both pure and mixed samples. Furthermore, the sensitivity of these primers remained consistent across both pure culture and blood samples, with the detection limit of the Ca2 primer pair ranging from 10 to 100 CFU/ml and the Ca3 primer pair ranging from 100 to 1,000 CFU/ml. Future work should focus on evaluating these primers in multiplex assays to further enhance their diagnostic utility.
Keywords: Mix-yeast infection, C. albicans, C.krusei, intercalating dye